ON THE CONCEPT OF SMALL AND MEDIUM-SIZED BUSINESSES - Z. Zargaryan (Вестник Северо-Кавказского федерального университета, 2022)
The article considers the main scientific and theoretical approaches to the use of the term «small and medium-sized businesses» in Russia and abroad, as well as the legal framework. The main problems of development of this sector are identified, and it is shown that small businesses are experiencing significant difficulties in the financial market. Along with the problems of lack of financial resources for enterprises that are at the stage of initial business organization, already functioning enterprises face the problem of access to sales markets, skills, and others. Some aspects of preferential lending to small and medium-sized businesses are considered.